Hagiographical Discourse in “Vita Pythagorica” by Yamblichus and “Vita Antonii” by Athanasius of Alexandria - Aleksandra S. Balakhovskaya (Studia Litterarum)
In the age of late Antiquity in the literatures of the Mediterranean basin countries hagiographic discourse has become widespread in pagan, Jewish and Christian literatures. Characteristic features of a literary work with a hagiographical discourse are the presence of a deified character (“man of God”), the combination of the historical substrate with the oral tradition, the dominance of pictorial elements over informative ones, the apologetic and edifying narrative, and the use of archetypes of the “man of God.” In addition to the general hagiographic discourse, there was the Christian hagiographic discourse, which has such specific features as a clear boundary between divine and human nature, the biblical paradigms underlying hagiographical texts, a more radical image of asceticism, the specific nature of miracles, which are mainly miracles of mercy and performed by the power of God. The article examines how the features of hagiographical discourse were reflected in the biographical works by Iamblichus “Vita Pithagorica” and by Athanasius of Alexandria “Vita Antonii,” and also shows the relations between Christian hagiography and the antique biography.